PREFORMULATION OF DICLOFENAC SODIUM SUSTAINED RELEASE BY ION EXCHANGER RESINE - A. Karim Zulkarnain; Tedjo Yuwono; Sumarno . (Indonesian Journal of Pharmacy, 2001)
The aim of the study was to find out a formula of granules giving a constant release of drug and also to search for the influence of pH on the drug release from the formula. One type of drug-resin complexes was used in this study ion exchanger the complex of diclofenac sodium and dowex. After 12 hours mixing the drug-resin complex was dried at 40 oC in an oven for 3 days. Afterwards, they were granulated and shieved. The particle size used were 20-40 mesh. The granules were tested for the dissolution of diclofenac sodium from the granules. The dissolution experiments were performed in a modified model of USP XX and the dissolution media used were phosphate buffer with the pHs of 5,8; 6,8 and 7.6 and the temperature was maintained at 37 oC. The amount of diug released in to the medium was assayed spectrophotometrically. The extent of dissolution was expressed as dissolution efficiency in 8 hours (DE8, % ). The results showed that the extent of dissolution of dtclofenac sodium from the granules complexed with the resin were low. The correlation between the amount of drug release from the complex and time was linier with the highest coefficient correlation having the ratio of l:5. The higher the pH values of the media, the higher the drug release from granules was. The drug release from drug-resin complex was well controlled which may be used for making a sustained release dosage form.Key Word : sustained release, diclofenac sodium, ion exchanger resin, granules